THE INFLUENCE OF SHARIA ACCOUNTING INFORMATION SYSTEMS ON THE FINANCIAL PERFORMANCE OF ISLAMIC FINANCIAL INSTITUTIONS: THE MEDIATING ROLE OF CUSTOMER TRUST AND COMPLIANCE - Tubarad, Chara Pratami Tidespania; Asmaranti, Yuztitya; Kesumaningrum, Ninuk Dewi (Faculty of Economics and Business, 2025)
This study examines the influence of Sharia Accounting Information System (SAIS) quality on the financial performance of Islamic financial institutions, considering customer trust and Sharia compliance as mediating variables. Using a quantitative explanatory design, data were collected from respondents representing managers, accounting staff, internal auditors, and active customers of Islamic financial institutions across Indonesia. The data were analyzed using SEM–PLS. The results demonstrate that SAIS quality positively and significantly affects financial performance, both directly and indirectly, through the mediating roles of customer trust and Sharia compliance. High-quality SAIS enhances information accuracy, timeliness, reliability, and integrity, thereby improving transparency, operational efficiency, and compliance with Islamic principles. Furthermore, customer trust strengthens institutional credibility, while adherence to Sharia principles reinforces ethical governance and social legitimacy, ultimately driving financial sustainability. This study contributes to the literature by integrating technological and spiritual dimensions into the Islamic financial performance model. It also extends the DeLone and McLean Information System Success framework by embedding faith-based constructs. The findings also provide practical insights for managers and regulators to improve digital governance and reinforce Sharia-compliant information systems in achieving competitive advantage and sustainable performance within the Islamic finance industry.